Corruption and Economic Growth in ASEAN Member Countries - Alfada, Anisah (Economics and Finance in Indonesia, 2019)
This study examines the effect of corruption on economic growth and determines the corruption threshold in nine ASEAN member countries in 1999-2016. This study assesses whether the effect of corruption is growth-enhancing or growth-deteriorating in different corruption threhsolds using a sample-splitting and threshold model. In contrast to the existing literature, this study does not group countries based on income level and therefore can reveal the corruption level of a country relative to a corruption threshold. The estimation results show that the adverse effect of corruption on economic growth is stronger for countries with corruption levels above the second threshold of 80.